The impact of foreign policy on educational exchange: the Swedish state scholarship programme 1938–1990. - Åkerlund, Andreas (Paedagogica Historica, 2014)
Programmes of international educational exchange are not only carried out for educational purposes, but form an important part of modern-day public diplomacy. Through exchange programmes education and research are linked with foreign policy interests, which then in turn should affect the international contacts of universities and research facilities. The present article applies a long-term perspective on the scholarship programme of the Swedish state in order to show how the shifts in Swedish foreign policy during the period 1938–1990 have affected the number and composition of scholars incoming to Sweden over time.